THE FUTURE OF THE GREEN ECONOMY: NATIONAL DEVELOPMENT ISSUES AND SOLUTIONS - Ashurova Oltin Yuldashevna; Qurbanov Muhammadali (Ecominds Press, 2025)
This article examines the concept of a green economy as an important tool for solving global environmental and socio-economic problems. The benefits of transitioning to a green economy for national development are described, including economic growth, social transformation, and environmental improvement. Particular attention is paid to the role of citizen participation and educational initiatives in transforming the economy. A sustainable future based on a green economy is not only a reality, but also a necessity to ensure the well-being of future generations.
Keywords: Green economy, sustainable development, renewable energy, environmental investments, social change, environmental technologies, circular economy.